An Improved Integrated Approach To Improving The Efficiency Of Energy Management Of Residential Buildings. (Journal of Architectural Design, 2024)
This article brings information about an improved comprehensive approach to improving the efficiency of energy management of residential buildings, a comprehensive approach to improving the energy efficiency of buildings, methods for assessing the effectiveness of energy-saving solutions